El delito de feminicidio y el principio de la responsabilidad penal de acto en el Código Penal Peruano - Nieves Ruiz, Gerhard (2019)
ABSTRACT The present thesis entitled: "THE CRIME OF FEMINICIDE AND THE PRINCIPLE OF THE RESPONSIBILITY OF ACT IN THE PERUVIAN CRIMINAL CODE" tackles the problematic about how the crime of feminicide affects the principle of responsibility of act in the Peruvian penal code. To state and verify the hypothesis, in the sense that "the crime of feminicide affects the principle of responsibility of act because its criminal-political justification constitutes a criminal law of the author"; has been addressed in the Theoretical Framework, titles referred to the Criminal Law of Act, Principle of Guilt, Theory of Punishment, the Crime of Feminicide and Comparative Legislation in the crime of Feminicide, for research, the universal method was used, general method comprising the deductive and inductive methods, and the specific method that develops the methods: synthetic, hermeneutic and analytical, which facilitates the study by decomposing each of the elements that make up the problem regarding how the crime of feminicide affects the beginning of liability of act in the Peruvian penal code. The investigation carried out, basically concludes by pointing out that the crime of femicide does affect the principle of liability of act in the Peruvian penal code, based on the following reasons: 1) Because a type sexualization is being gestated, that is to say, To identify only and exclusively the male as the perpetrator of the crime of feminicide, the principle of responsibility for the act is violated, as well as a clear contradiction with the stipulated in our preliminary title, which states that the penalty can not exceed the responsibility for the fact. 2) Due to its relationship with the apparent competition of laws between the crime of femicide and parricide, given that the cases regulated in the crime of feminicide can easily be subsumed in the criminal types established in the Criminal Code, such as the parricide, since the latter extended its scope, incorporating modifications such as: "... sanction behaviors with or without a current sentimental relationship", precisely to stop violence against women, and 3) Due to the non-existence of compatibility between the principles of culpability and equality and the regulation of the crime of femicide in the Peruvian penal code, given that a person is being punished on the basis of their personal characteristics, and not because of the act committed in itself, which has led to the creation of a psyche social, where the mere condition of man (personal condition, sex) would become a presumption of guilt or greater culpability.